(untitled) (American Journal of Business Management, Economics and Banking, 2024)
Tourism has become one of the most rapidly evolving industries globally, with smart tourism technologies (STTs) increasingly influencing how destinations are marketed, managed, and experienced by visitors. For developing nations like Uzbekistan, leveraging these technologies offers both opportunities and challenges. While much of the global conversation has focused on the adoption of STTs in developed regions, there has been less research dedicated to their impact in emerging markets. The unique cultural and historical assets of Uzbekistan, coupled with its government’s drive to boost tourism, make it an ideal case study for exploring the effects of STTs on tourist satisfaction and loyalty.